Channichthys mithridatis, a new species of icefishes (Perciformes: Notothenioidei: Channichthyidae) from the Kerguelen Islands (East Antarctica), with comments on the taxonomic status of Channichthys normani - Shandikov, G.A.; Шандиков, Г.О. (V.N.Karazin Kharkiv National University (Kharkiv, Ukraine), 2008)
The sub-Antarctic genus Channichthys, endemic for the area of the Kerguelen-Heard Plateau of the Southern Ocean, includes 7 nominal species of unicorn icefishes: C. rhinoceratus Richardson, 1844, C. rugosus Regan, 1913, C. velifer Meissner, 1974, C. panticapaei Shandikov, 1995, C. irinae Shandikov, 1995, C. bospori Shandikov, 1995 and C. aelitae Shandikov, 1995. The last four were described on the basis of materials collected by the 1990 research expedition (the 23rd cruise of R/V Professor Mesyatsev) of YugNIRO to the Kerguelen Islands area. The lately described C. normani Balushkin, 1996 is considered to be a junior synonym of C. panticapaei. In the present paper a new, the eighth species of genus Channichthys is described – C. mithridatis sp. n. – green icefish (on the basis of 29 specimens), collected in the same (R/V Professor Mesyatsev) cruise. The new species is closely related to C. irinae, but in the most differs from it by the uniserial gill-rakers, frequency distribution and greater number of spines in first dorsal fin, relatively smaller eye, large mouth and by traits of biology – C. mithridatis is piscivorous, while C. irinae is a typical zooplankton consumer.
Channichthys mithridatis – новий вид білокровних риб (Perciformes: Notothenioidei: Channichthyidae) від островів Кергелен (Східна Антарктика), з коментарями про таксономічний статус Channichthys normani
Поширений у Південному океані ендемічний для шельфових вод островів Кергелен та Херд й таласобатіалі банок підводного хребту Кергелен-Херд субантарктичний рід білокровних риб Channichthys об’єднує 7 номінальних видів білокровок: носорогу білокровку C. rhinoceratus Richardson, 1844, руду білокровку C. rugosus Regan, 1913, парусну білокровку C. velifer Meissner, 1974, вугільну білокровку C. panticapaei Shandikov, 1995, карликову білокровку C. irinae Shandikov, 1995, більшооку білокровку C. bospori Shandikov, 1995 та білокровку «Аеліти» C. aelitae Shandikov, 1995. Останні 4 види були описані за матеріалами колекції, зібраної автором біля островів Кергелен у 1990 р. під час науково-дослідної експедиції ПівденНІРО (23-й рейс НДС «Профессор Месяцев»). Щодо виду Channichthys normani Balushkin, 1996, пізніше описаного від островів Кергелен, то він розглядається як молодший синонім C. panticapaei. У цій роботі описано (за 29 екз.) новий, 8-й вид роду Channichthys – C. mithridatis sp. n. (зелена білокровка), здобутий у тім же рейсі НДС «Профессор Месяцев» у 1990 р. Новий вид морфологічно найбільш близький до C. irinae, але відрізняється від нього головним чином однорядними зябровими тичинками, розташованими тільки на зовнішньому боці зябрової дуги, частотою розподілення та більшим числом колючих променів у 1-му спинному плавці, відносно меншим діаметром ока, більшим ротом, забарвленням та особливостями біології – C. mithridatis – рибоїдний хижак, тоді як C. irinae – типовий зоопланктофаг, у шлунках якого відмічені евфаузієві рачки Thysanoessa macrura.
Keywords: green icefish; endemic; Southern Ocean; Kerguelen-Heard Submarine Ridge; biology; stages of gonad maturity; зелена білокровка; ендемік; Південний океан; підводний хребет Кергелен-Херд; біологія; стадії зрілості гонад